PRESENCE OF PAIN IN ELDERLY PEOPLE PERFORMING PHYSICAL ACTIVITY BEFORE AND DURING COVID-19 PANDEMIC IN THE INTERIOR OF AMAZONAS (Movimenta (ISSN 1984-4298), 2023)
Introduction: Social isolation due to Covid-19 impacted the practice of physical activity and, in some cases, led to the adoption of sedentary behavior among the elderly. This fact can lead to problems such as increased pain intensity. The practice of physical activity seems to contribute to the reduction of this symptom in this population. Objective: To describe and characterize the presence of pain in elderly people who practice physical activities in the interior of Amazonas in two periods: before and during the Covid-19 pandemic. Materials and Methods: This is a longitudinal study, with a sample of 66 elderly people who practiced physical activities twice a week. Data related to pain level were collected using numerical and facial scales. For data analysis, Microsoft Office 365 and IBM/Stata MP, version 14.0, were used. Results: The results obtained in the evaluation carried out using the numerical scale demonstrate that there was a significant reduction in pain intensity (p
Keywords: Pain; Physical Activity; Pandemic; Ageism